(untitled) (Proceeding of the International Conference on Arts and Humanities, 2023)
The media artist Refik Anadol’s acclaimed work Machine Memoirs: Space inaugurates the first permanent immersive digital art gallery in the UK, The Real Store. Utilizing machine intelligence to recreate images of the International Space Station, telescopes and NASA satellites, Machine Memoirs: Space provides viewers with an immersive experience of lush visuals and stunning 3D sound, allowing them to experience the spectacle of various spaces. In the age of artificial intelligence, when time and space can be transformed into multiverse experiences by machines, what does it mean to be human? Similarly, a central theme of Andreas Broeckmann’ s book Machine Art in the Twentieth Century is how machines impact the interaction between humans and artistic creations. This book is the first comprehensive study of machine art, examining the aesthetics of machines in art. Within the theoretical framework of Andreas Broeckmann, this study argues that machine-based algorithms in artworks create spectacular artistic experiences through synesthesia between machines and humans. Additionally, the challenge for the human subjectivity is posed by the technicity of visual perceptions. The contributions of this study are divided into two aspects. The investigation of Refik Anadol’s works may contribute towards a better understanding of the theoretical framework of machine art. Additionally, the explanation of the relationship between technology, humans and artworks provides some clues for future digital art creations.